Ruxolitinib synergizes with regulatory T cells to improve inflammation but has no added benefits in decreasing albuminuria in SLE - Lyu, Mi-Ae; Tang, Ximing; Raso, Maria Gabriela; Huang, Meixian; Zeng, Ke; Sadeghi, Tara; Flowers, Christopher R.; Parmar, Simrit (Frontiers in Immunology, 2025)
BackgroundUmbilical cord blood (UCB)-derived CD4+CD25+CD127low regulatory T cells (Tregs) can decrease albuminuria and anti-dsDNA IgG in systemic lupus erythematosus (SLE). Ruxolitinib, a JAK/STAT inhibitor, has been shown to improve cutaneous manifestations of SLE. We hypothesize that the addition of ruxolitinib to UCB-Tregs may improve SLE outcomes.MethodsIn vitro cell suppression, phenotype change, IL-10 secretion, and cytokine levels in coculture supernatants were determined to quantify the impact of adding ruxolitinib to UCB-Tregs. A xenogeneic SLE model was utilized to study their in vivo combination.ResultsIn a dose-dependent manner, ruxolitinib addition synergizes with UCB-Tregs to suppress SLE-PBMC proliferation, inhibit CD8+ T cells, and reduce phosphorylation of STAT3/STAT5/AKT in CD8+ T cells. UCB-Treg and ruxolitinib combination also downregulates the soluble form of inflammatory cytokines including IFN-γ, IP-10, TNF-α, IL-6, sCD40L, IL-17A, IL-17F, IL-1α, and LIF in cocultures. The addition of ruxolitinib increases UCB-Treg cell persistence in peripheral blood in vivo and decreases the soluble form of human inflammatory cytokines including IFN-γ, TNF-α, and sCD40L in plasma along with improvement of skin lesions in SLE xenografts. Compared to control, significantly lesser CD3+, CD4+, CD8+, and Ki-67+ infiltrates are observed in the lung and kidney of UCB-Tregs and/or ruxolitinib recipients. No added benefit of addition of ruxolitinib is observed on the significant improvement in the urine albumin/creatinine ratio and the anti-dsDNA IgG levels induced by UCB-Tregs.ConclusionsOur results demonstrate that the addition of ruxolitinib to UCB-Tregs increases UCB-Tregs suppressor function and their persistence in vivo, downregulates systemic inflammation, and controls cutaneous SLE but does not add to UCB-Treg-mediated improvement in renal manifestations.